Pengaruh integriti anggota Polis Diraja Malaysia terhadap budaya organisasi di kontinjen Perak: Tindakan organisasi sebagai moderator - Megat Ayop, Megat Arifin (2025)
In order to guarantee the security of the country, the formation of a security force is very necessary to carry out duties, trust and responsibility like the Royal Malaysian Police (PDRM). The PDRM must shoulder responsibility fairly, justly and decisively to ensure the formation of the life of the community and the country in a state of peace, safety and not be disturbed by unwanted elements. The goal can be achieved by implementing an effective service delivery system and the practice of integrity values in the PDRM team. The importance of integrity to the PDRM can make this country's policing delivery system more efficient and disciplined. Therefore, this study aims to identify the influence of the integrity of PDRM members on the organizational culture in the Perak contingent. Quantitative and qualitative approaches were used with the involvement of 700 PDRM members. By using SEM-PLS analysis, there are four main findings for this study, (1) PDRM members take serious steps and will report cases, (2) there is a significant difference in judging a case as serious and reporting a case based on demographics, (3) organizational actions are able to act as moderators and (4) there is only one variable that affects the integrity of PDRM members which is personality. The findings also found that improvement or change is the best method in improving the integrity of PDRM members. By using Theory of Police Organizational Integrity, this study can provide a more comprehensive policy or policy in improving integrity in uniformed forces, especially the PDRM.